South Africa - IOSCO Principles--Securities Markets : Detailed Assessment of Implementation - International Monetary Fund; World Bank (Washington, DC, 2013)
This is an update of the International Organization of Securities Commissions (IOSCO) assessment that was performed in 2000 as part of the Financial Sector Assessment Program (FSAP) of South Africa. South Africa has made substantial progress in addressing the recommendations of the 2000 FSAP and is continuing to build upon these accomplishments. South Africa was one of the first countries to adopt the International Financial Reporting Standards promulgated by the International Accounting Standards Board. The Department of Trade and Industry (DTI) has the legal authority to register all companies in South Africa, including public companies and to set and enforce disclosure requirements and accounting standards. Significant amendments to the Companies Act dealing with this responsibility were enacted in 2007 and recently in 2009. DTI has not implemented the 2007 or 2009 amendments. Going forward, careful examination should be given to whether the authority and responsibility for these functions should continue in the DTI or be reassigned by Parliament to the Financial Services Board (FSB).